Adsorption of cresols on zinc-aluminium hydroxides - a comparison with zeolite-X - Vijayakumar, J.; Chikkala, Suresh K.; Mandal, Sujata; Mayadevi, S. (Separation Science and Technology, 2011)
Liquid phase adsorption of m-cresol on Zn-Al hydroxide adsorbents with three different Zn/Al molar ratios was studied in different solvents and compared with commercial zeolite 13X. Among the three adsorbents, ZA-16 showed adsorption capacity similar to commercial zeolite 13X. Solvents used for the preparation of m-cresol solution were found to influence the adsorption capacity. The adsorption capacity was maximum for the solution of m-cresol in n-hexane. Conventional Langmuir and Freundlich adsorption isotherm equations were used to explain the adsorption behavior. The kinetics of m-cresol adsorption followed the first-order Lagergren kinetic model. p-Cresol/m-cresol separation factor was the highest when toluene was used as the organic medium.
Keywords: Adsorption; cresol; zeolite; zinc-aluminium hydroxide